2020
DOI: 10.1017/s1460396920000394
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapeutic management of brain tumours during the COVID-19 pandemic

Abstract: Aim: The coronavirus disease (COVID-19) pandemic is bound to put tremendous pressure on the existing healthcare system. This aim of this technical note is to help in triaging patients with brain tumours who are sent for radiotherapy during this pandemic and to provide safe and evidence-based care. Materials and Methods: Published data for this review were identified by systematically searching PubMed database from November 2007 onwards with the following Medical Subject Heading (Mesh) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…in poor PS) Anaplastic oligodendroglioma (up to 4-6 month) Continue any progressing RT: High priority: Large benign tumors with acute symptoms (pressure, loss of sight); posterior fossa tumors (malignant or non-malignant) causing life-threatening hydrocephalus. High-intermediate priority: Medulloblastoma; Young Grade 3 glioma Intermediate priority: High-grade glioma in young fit patients Low priority: Small benign tumors; HGG in elderly, low-grade glioma ( Neuro-oncology treatment guidance during COVID-19 pandemic, 2021 ) High-Grade Glioma: Standard of care (surgical resection followed by RT) Considerable tumor volume (gliomatosis) Involvement of brainstem/spinal cord Grade III astrocytoma Delicate or older patients: Hypo-F accelerated course (34 Gy /10 frs or 40.05 Gy / 15 frs and 25 Gy / 5 frs for smaller tumors) IDH-wild-type and IDH-mutant glioma: shorten RT courses ( Vordermark, 2020a ) Low-grade glioma asymptomatic meningioma G1-2 Glioblastoma, Frail/elderly (40 Gy / 15 frs or 25 Gy / 5 frs) ( Kochbati et al, 2020 ) GBM: - Aged ≥ 65 yrs with excellent PS: Hypo-F RT (40 Gy /15 frs) - Aged < 65 yrs with good PS (KPS ≥ 70): standard fractionation (60 Gy / 30 frs) -Poor PS (KPS < 50): palliative regimens (34 Gy /10 frs or 25 Gy /5 frs) ( Noticewala et al, 2020b ) GBM: Elderly with poor KPS/unmethylated - Grade 1, Grade 2, and Grade 3 meningiomas - Schwannomas - Low-grade gliomas - Meningioma: (Hypo-F RT) Grade 1, Grade 2: 25 Gy / 5 frs Grade 3: 45 Gy in 15 fractions -Schwannomas: frameless SRS/ Hypo-F RT (25 Gy / 5 frs) -GBM: Elderly with poor KPS/methylated: 34 Gy /10 frs or 5 Gy weekly × 6 weeks Younger patients good KPS: Hypo-F RT (60 Gy / 20 frs (SIB technique) -Medulloblastoma: Start with posterior fossa boost and then switch over to craniospinal RT with VMAT/IMRT -Cystic craniopharyngiomas: For all post-op patients, start on RT ( Balakrishnan et al, 2020 ) Asymptomatic meningioma grade I-II Asymptomatic AVM Grade 3 glioma (anaplastic oligodendroglioma) for 4-6 months Non-co-deleted (anaplastic astrocytoma) Hypo-F RT: 40 Gy/15 frs or 30 Gy/6 frs ( Hinduja et al, 2020 ) …”
Section: Resultsmentioning
confidence: 99%
“…in poor PS) Anaplastic oligodendroglioma (up to 4-6 month) Continue any progressing RT: High priority: Large benign tumors with acute symptoms (pressure, loss of sight); posterior fossa tumors (malignant or non-malignant) causing life-threatening hydrocephalus. High-intermediate priority: Medulloblastoma; Young Grade 3 glioma Intermediate priority: High-grade glioma in young fit patients Low priority: Small benign tumors; HGG in elderly, low-grade glioma ( Neuro-oncology treatment guidance during COVID-19 pandemic, 2021 ) High-Grade Glioma: Standard of care (surgical resection followed by RT) Considerable tumor volume (gliomatosis) Involvement of brainstem/spinal cord Grade III astrocytoma Delicate or older patients: Hypo-F accelerated course (34 Gy /10 frs or 40.05 Gy / 15 frs and 25 Gy / 5 frs for smaller tumors) IDH-wild-type and IDH-mutant glioma: shorten RT courses ( Vordermark, 2020a ) Low-grade glioma asymptomatic meningioma G1-2 Glioblastoma, Frail/elderly (40 Gy / 15 frs or 25 Gy / 5 frs) ( Kochbati et al, 2020 ) GBM: - Aged ≥ 65 yrs with excellent PS: Hypo-F RT (40 Gy /15 frs) - Aged < 65 yrs with good PS (KPS ≥ 70): standard fractionation (60 Gy / 30 frs) -Poor PS (KPS < 50): palliative regimens (34 Gy /10 frs or 25 Gy /5 frs) ( Noticewala et al, 2020b ) GBM: Elderly with poor KPS/unmethylated - Grade 1, Grade 2, and Grade 3 meningiomas - Schwannomas - Low-grade gliomas - Meningioma: (Hypo-F RT) Grade 1, Grade 2: 25 Gy / 5 frs Grade 3: 45 Gy in 15 fractions -Schwannomas: frameless SRS/ Hypo-F RT (25 Gy / 5 frs) -GBM: Elderly with poor KPS/methylated: 34 Gy /10 frs or 5 Gy weekly × 6 weeks Younger patients good KPS: Hypo-F RT (60 Gy / 20 frs (SIB technique) -Medulloblastoma: Start with posterior fossa boost and then switch over to craniospinal RT with VMAT/IMRT -Cystic craniopharyngiomas: For all post-op patients, start on RT ( Balakrishnan et al, 2020 ) Asymptomatic meningioma grade I-II Asymptomatic AVM Grade 3 glioma (anaplastic oligodendroglioma) for 4-6 months Non-co-deleted (anaplastic astrocytoma) Hypo-F RT: 40 Gy/15 frs or 30 Gy/6 frs ( Hinduja et al, 2020 ) …”
Section: Resultsmentioning
confidence: 99%
“…Several factors, namely age, performance status, histology, surgery and history of post-operative adjuvant therapy contribute to the course of disease. In neuro-oncology, radiotherapy plays an important role in the management of brain tumors [6] . It is important for neurosurgeons to understand not only on how to administer it in general, but also about what and when to give it to patients with various diseases, including COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Glioma patients and families admitted to the hospital should be educated to wash their hands properly, wear protective masks, and be assisted by one family member only. [ 4 ]…”
Section: Surgery Indication In Glioma Patient During Covid-19 Pandemicmentioning
confidence: 99%
“…[ 2 , 3 ] Case fatality rate for cancer patients compared to non-cancer patients in the absence of COVID-19 is 5,6:2,1. [ 4 ] The study conducted by Liang et al . in cancer patients during COVID-19 pandemic showed that 38% had a higher risk of severe events.…”
Section: Introductionmentioning
confidence: 99%